Preparation of value-added formulations of selected Ksheerapakas by trial and error method - Indu Sabu; S Krishna Rao; Gurucharan Bhuyan; Banamali Das; Meda Mruthyumjaya Rao (Wolters Kluwer Medknow Publications, 2023)
Introduction: In Ayurvedic classics, the potential of herbal medicine is expressed through various dosage forms having multilevel actions. Ksheerapaka is one of the unique preparations of Ayurveda pharmaceutics, where milk is used as the medium for formulation. In general, Ksheerapaka is prepared by boiling the drug with a specific quantity of milk and water and reducing it to quantity. The preparation of ksheerapaka is time-consuming. As milk is the medium of preparation, the stability of the product is low and not travel-friendly. Due to these flaws, a new patient-friendly formulation with less bulk and better stability is intended to be prepared by value addition. Methods: A literature review was done on commonly used ksheerapaka and the value addition of milk products. Three commonly used Ksheerapakas, namely, Arjuna, Sthira, and Lasuna, were selected and prepared by the classical method. Value addition was done by trial and error using different techniques in three different centers. Result and Conclusion: Ksheerapaka prepared by spray drying had the same flavor and taste as the classical preparation and was free-flowing without any grittiness. The appearance and taste were appreciable and easily dissolvable. The product was also stable at room temperature. Spray drying can be recommended for the commercial preparation of Ksheerapaka powder considering the product's cost-effectiveness and efficacy. Unlike other value-added preparations of classical Ayurvedic formulations, Ksheerapaka powder also satisfies the mode of administration like the classical preparation.